INFORMATION LITERACY UNTUK PEMBELAJARAN DI PENDIDIK.AN TINGI - Utami, Dina (MAJALAH ILMIAH PEMBELAJARAN, 2007)
Information af.re is marked with the abundant of information. It is opportunities and challenge as well. Jn higher education, students deal with this information in their everyday live. Information literacy gives students the ability to retrieve, evaluate, communicate, and used the information available out there effectively. Information literacy gives great contribution to create life long learners. Considering it 's importance, higher education should equipped their students with information literacy, incorporated in it 's curriculum and pedagogy.